ABT-737 and Roscovitine induces apoptosis in a synergistic fashion in mast cells carrying the D816V KIT mutation. Issue 5 (2015) - Lyberg, Katarina; Nilsson, Gunnar; Westerberg, Christine Möller
No abstract available